Constructing Indonesian Digital Economy Index in Determining Economic Policy Priorities amidst the Covid-19 Pandemic - Sari, Diah Rukmana; Nasrudin, Nasrudin (UI Scholars Hub, 2022)
The constant increase in the number of internet users in Indonesia amid a sluggish economy caused by the Large-Scale Social Restriction (PSBB) policy is a great opportunity for a digital-based economy. However, the unavailability of relevant macroeconomic statistical measurements inhibits the digital economy from being determined as a policy priority amidst the Covid-19 pandemic. This study offers an alternative measurement of the digital economy of Indonesia by establishing Digital Economy Index (DEI). This study discovers that digital economic activities in Indonesia have grown rapidly with an average growth of almost nine percent quarterly. On the other hand, this study also utilizes the established index to determine its effect on the economy using the Error Correction Model (ECM). The analysis reveals that DEI has not affected GDP in the short term, but it has significantly and positively in the long term. Therefore, the government can apply this digital economy index to describe the development of digital economic activities to support the digital economy as a priority for economic policy amidst the Covid-19 pandemic.